Adolescent identity: The importance of the social history. (August 2020) - Silverstein, Laura; Zander, Emily; Middleman, Amy B
This is a unique case of a patient with trichotillomania, depression, and anxiety for 2 years, serving as coping strategies for underlying gender dysphoria. To our knowledge, a case of a patient presenting with this unique constellation of comorbid conditions has not previously been reported. This case stresses the importance of providers obtaining a full social history consistently and repeatedly while providing a nonjudgmental environment for patients to disclose sensitive and potentially fluid information related to gender identity and sexuality.